Medias et imperialisme culturel: le cas du Burkina Faso - Balima, Serge Théophile (Afrika Focus, 2001)
The various kinds of information released in the press and other media are cultural products that partake in the shaping of citizens’ opinions and minds. Radio and television in particular present their audiences in Burkina Faso with various life-styles through diverse entertainment programmes which have grown popular among the urban population. These are fertile fields for cultural imperialism in the country. In the on-going process of internationalization of culture facilitated by the new communication technology, the cultural identity of Africans is increasingly threatened. This phenomenon is the result of adverse political and economic conditions with significant cultural consequences. In the long run, these cultural consequences will lead to the marginalization of Africa on the international scene and its increased dependence on the western powers. Key Words: culture, imperialism, influence, information, media, uniformity.